ANALISIS PENGGUNAAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN PELAYANAN PUBLIK PT POS INDONESIA - Adella Franscillia Samma; Kheyene Molekandella Boer (An-Nida : Jurnal Komunikasi Islam, 2023)
Analyze the use of information technology in improving the public service of PT Pos Indonesia in the border area of Nunukan Regency, North Kalimantan. This study used descriptive qualitative method. The research focuses include transparency, participation, and efficiency. Data collection techniques were carried out by interviews and documentation. Data analysis techniques were carried out by means of data reduction, data presentation, and drawing conclusions. The results of the study show that the use of information technology in improving the public service of PT Pos Indonesia in the border area of Nunukan Regency, North Kalimantan, is carried out in three main steps, namely transparency, participation and efficiency. The transparency process carried out by PT Pos Indonesia in the border area of Nunukan Regency to improve public services is by making Standard Operating Procedures (SOPs), creating information about how to use the application, and highlighting three main characteristics in services, namely easy access, authentic evidence. , and the principle of honesty. The participatory process carried out by PT Pos Indonesia in the border area of Nunukan Regency to improve public services is to create a complaint service and provide responses to any input provided. The efficiency process carried out by PT Pos Indonesia in the border area of Nunukan Regency is carried out in several steps, namely by updating the application and secondly by minimizing errors in the service process. This process has been able to improve public services, because it can be proven by the number of Pospay application users up to 79 partners and Pos Remittance totaling 15 partners with details of 7 money order partners and 8 money order partners.